Women and Financial Independence: Analysis of Implications for Negotiation of Power in The Household - Igirisa, Silvia Febriyanti; Andriyanto, Andriyanto (Syntax Literate, 2024)
Women's financial independence has become an important issue in recent decades. As women's participation in the workforce increases, they have greater control over their own finances and can make more independent decisions about their lives. This can have significant implications for power dynamics in the household and relationships between women and men. The aim of this research is to analyze the implications of women's financial independence on power negotiations in the household. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that women's financial independence has complex implications for power negotiations in the household. In some cases, women's financial independence can increase their bargaining power in negotiations with their partners and lead to positive changes in their relationship dynamics. However, in other cases, women's financial independence can cause tension and conflict in the household.